Clinical evaluation of injectable progestins long term - Onetto, Enrique (2015)
A comparative clinical evaluation of a comprehensive contraceptive program that began in 1964 in the areas of Health North and West of Santiago, was made using theoretical methods of life up to 36 months of use. Lippes Loop-D were inserted intermenstrually to 14,579 women; TCu-200 (only 12 months of use) to 350 women; Medroxyprogesterone Acetate was administered intramuscularly in dose of 150 mg. every 3 months 561 women and 300 mg. every six months to 588. The percentage of patients who discontinued treatment were influenced mainly by age, similarity and the desire for future pregnancies.